A Novel Nondevelopmental Role of the SAX-7/L1CAM Cell Adhesion Molecule in Synaptic Regulation in Caenorhabditis elegans. Issue 2 (8th December 2014) - Opperman, Karla; Moseley-Alldredge, Melinda; Yochem, John; Bell, Leslie; Kanayinkal, Tony; Chen, Lihsia
Abstract: The L1CAM family of cell adhesion molecules is a conserved set of single-pass transmembrane proteins that play diverse roles required for proper nervous system development and function. Mutations in L1CAMs can cause the neurological L1 syndrome and are associated with autism and neuropsychiatric disorders. L1CAM expression in the mature nervous system suggests additional functions besides the well-characterized developmental roles. In this study, we demonstrate that the gene encoding the Caenorhabditis elegans L1CAM, sax-7, genetically interacts with gtl-2, as well as with unc-13 and rab-3, genes that function in neurotransmission. These sax-7 genetic interactions result in synthetic phenotypes that are consistent with abnormal synaptic function. Using an inducible sax-7 expression system and pharmacological reagents that interfere with cholinergic transmission, we uncovered a previously uncharacterized nondevelopmental role for sax-7 that impinges on synaptic function.